An investigation of the neuroregulation and circadian expression of brown fat heat production. - Kelly, Lisa Ann. (University of Ottawa (Canada), 1995)
The overall aim of this work is to gain insight into the physiological role of brown adipose tissue (BAT) thermogenesis in thermoregulation; to that end, the studies reported here comprise an investigation, in the rat, of both the neural control of interscapular brown fat and the daily pattern of BAT temperature change in the rat. In the first experiment, an acute stimulation paradigm was employed in combination with moveable electrodes, in order to precisely map the ventromedial hypothalamus (VMH) for sites which elicit stimulation-induced increases in BAT thermogenesis. Of roughly 30 stimulated sites in the VMH region, 20% gave rise to a BAT response; temperature rises ranged from 0.6 to 4.6$\sp\circ$C, and returned to baseline in approximately an hour. In the course of this first study, stimulation of a number of extra-VMH sites was observed to evoke a rapid drop in BAT temperature, a response which has not been well-characterized. Therefore, in the second study, structures outside the VMH were systematically evaluated, using moveable electrodes, for sites associated with a BAT temperature decrease. About 70% of electrode tracks located in the ventral lateral thalamic nucleus (VLT) and the zona incerta (ZI) displayed sites which elicited repeatable drops in BAT temperature. The typical profile showed a temperature drop of approximately 0.5$\sp\circ$C, and took about 30 min drop in core temperature. To investigate the daily pattern of BAT temperature changes, radio-frequency disc transmitters (Mini-Mitter Co., Inc.) were implanted beneath the interscapular BAT deposit, and temperatures were recorded throughout the 24 h cycle of equal light/dark periods, for up to six days. As expected, all data show a circadian cycle; the analysis confirms the strong visual impression given by the temperature profiles of an elevated nocturnal baseline. However, the presence of ultradian rhythms is less clear; spectral analysis suggests that the 8h and 4h cycles are most consistent, and the 4h cycle may be the stronger as it persists in the analysis of the deseasoned data. Three subjects also had a second transmitter placed in the intraperitoneal cavity in order to collect simultaneous core and BAT temperature. The temperature profiles we observe appear to be highly correlated; both the BAT and core patterns are characterized by an elevated nocturnal baseline, peaks and valleys throughout the 24h, and an anticipatory rise in temperature that appears about three hours before light offset. This latter feature, along with the persistence of the BAT nocturnal rise even in the 24h lights-on condition, suggests that BAT temperature rhythm is driven by an endogenous pacemaker, similar to the regulation of core temperature. (Abstract shortened by UMI.)
Keywords: Biology, Neuroscience.